Targeting post-translational modifications of histones for cancer therapy - Hsu, Y-C; Hsieh, Y-H; Liao, C-C; Chong, L-W; Lee, C-Y; Yu, Y-L; Chou, R-H (Cellular and Molecular Biology, 2015)
Post-translational modifications (PTMs) on histones including acetylation, methylation, phosphorylation, citrullination, ubiquitination, ADP ribosylation, and sumoylation, play important roles in different biological events including chromatin dynamics, DNA replication, and transcriptional regulation. Aberrant histones PTMs leads to abnormal gene expression and uncontrolled cell proliferation, followed by development of cancers. Therefore, targeting the enzymes required for specific histone PTMs holds a lot of potential for cancer treatment. In this review article, we retrospect the latest studies in the regulations of acetylation, methylation, and phosphorylation of histones. We also summarize inhibitors/drugs that target these modifications for cancer treatment.